Assessment of Radon and Naturally Occurring Radionuclides in the Vredefort Meteorite Crater in South Africa - Rikus le Roux; Jacques Bezuidenhout (Atmosphere, 2023)
The concentric impact rings of the Vredefort Crater contain rocks with elevated uranium concentrations resulting from the geological signature of a meteoric impact. The decay of this uranium was estimated to lead to elevated indoor radon concentrations in the Crater, but such a study has never been carried out. This study explores the relationship between the natural radionuclides i-0found in the geology of the Vredefort Crater and indoor radon concentrations. This was achieved through soil sampling and radionuclide surveys conducted on three impact rings, supplemented by indoor radon measurements in dwellings found in the area. In situ measurements revealed that one impact ring had higher-than-average uranium concentrations at 50 Bq/kg. Surprisingly, the measured indoor radon levels were lower than expected (113 Bq/m3). These measurements were taken during the COVID-19 pandemic and colder months, conditions that would typically result in elevated indoor radon levels. Soil samples indicated uranium activity of 30 Bq/kg, comparable to the world average of 35 Bq/kg. However, defunct mine tunnels in the area exhibited elevated radon concentrations, averaging 364 Bq/m3. The disparity between expected and measured indoor radon levels was attributed to the composition of surficial deposits, bedrock, and architectural features of the dwellings preventing radon accumulation.